Cathodal stimulating the left DLPFC changes risk disposition toward common risky behaviors in daily-life. (14th September 2019) - Wen, Yatong; Turel, Ofir; Peng, Youqing; Lv, Chenyu; He, Qinghua
Highlights: Two studies were performed with HD-tDCS over the left DLPFC with naïve subjects. Cathodal tDCS reduced attitudes and intentions toward risky behaviors. No changes in attitudes and intentions were found toward control behaviors. The reductions were larger in the tDCS group than in the sham group. Results highlight the importance of left DLPFC in mediating daily risky behaviors. Abstract: Many daily activities require the weighting of risks and gains, and adjusting decisions based on this information. The present study investigates the role of left DLPFC in such normal-life, routine, but risky decisions. We expected that down-regulating the left DLPFC will reduce emphasis on gains such that less-riskier decisions, as captured with attitude and behavioral intention measures, are made. In study 1 (n = 56), tDCS naïve participants were recruited and subjected to high-definition cathodal tDCS stimulation (with intensity of 1.5 mA for 20 min) of the left DLPFC. A single-blind within-subject pre-post design was employed, in which each subject responded to realistic, normal life, risky decision and control scenarios, before and after stimulation. In study 2 (n = 60), we added a between-subjects factor by assigning half of the participants to a sham stimulation condition. Results were consistent across studies. They demonstrated significantly reduced attitudes and intentions toward risky behaviors, and no significant changes in attitudes and intentions toward control behaviors. Study 2 showed that the reductions were significantly larger in the tDCS stimulation group than in the sham group. These results highlight the role of the left DLPFC in mediating common daily risky behaviors.